Annual variation in thermal and structural properties of yesso scallops (Mizuhopecten yessoensis) adductor muscle - Tian, Yuanyong; Jiang, Minghui; Wang, Zhuolin; Yuan, Chunhong (Frontiers in Sustainable Food Systems, 2024)
The annual changes of the scallop’s adductor muscle in Ca2+-ATPase activity, chymotryptic digestion, endogenous fluorescence spectra, sulfhydryl content, and surface hydrophobicity were studied. Ca2+-ATPase activity peaked in February and reached its minimum in August for males and in July for females. However, no significant differences were observed between males and females throughout the year. The inactivation rate of Ca2+-ATPase activity increased by 17- to 36-fold when the temperature rose from 38°C to 45°C. The ratio of free myosin to bound myosin was approximately 5:4 at 0.5 M KCl and changed to 5:1 at 1.0 M, as determined by modeling. Chymotryptic digestion demonstrated that scallop myosin could be cleaved into S-1/rod portions at 0.1 M and HMM/LMM at 0.5 M KCl. Furthermore, no significant seasonal variations were observed in chymotryptic digestion patterns, endogenous fluorescence, surface hydrophobicity, or sulfhydryl content. In conclusion, the structure and thermal stability of both male and female scallops remained stable throughout the year, making them suitable for processing and preservation.